PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING ( Studi Pada Perusahaan Manufaktur Sektor Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2016) - Susantika, Bingah; Mahfud, Mohammad Kholiq (Faculty of Economics and Business Diponegoro University, 2019)
This study aims to analyze the factors that effects capital structure with profitability as the intervening variable on Miscellaneous Industry Sector in Indonesia Stock Exchange (IDX) in the 2012 -2016 period. Debt to Equity Ratio (DER) is the dependent variable in this study. There are three independent variables used, they are Firm Size (SIZE), Asset Structure (AS), Current Ratio (CR), and Return on Asset (ROA) as the intervening variable.The population used in this study consisted of Miscellaneous Industry Sector listed on IDX in the 2012-2016 period, bringing total population is consist of 44 companies. The sampling in this study using purposive sampling, so that the total samples are 18 companies. The data analysis methods which are used is the classical assumtion test, path analysis and Sobel Test to analyze the mediation effect of the intervening variable.The result of this study shows that SIZE has insignificant positive effect to ROA, CR has significant positive effect to ROA, and AS has significant negative effect to ROA. SIZE, CR, AS, ROA have significant negative effect to DER. ROA can’t mediate the effect of SIZE and CR to DER, while the ROA may mediate the effect of AS to DER.